INSULIN-MEDIATED REGULATION OF MUSCLE PROTEIN TURNOVER IN HEALTHY HUMANS - Staples, Aaron W. (My University, 2009)
Only basal concentrations of insulin (i.e., 3-10 μUml-1) appear to be required for the maximal stimulation of muscle protein synthesis (MPS) during sustained hyperaminoacidemia in healthy adult humans at rest and during resistance exercise recovery. Whether plasma insulin at greater than basal concentrations can further stimulate MPS after the feeding of an MPS-saturating bolus dose of whole protein remains unexplored. We investigated the potential for insulin, via increased carbohydrate consumption, to augment mixed MPS, femoral artery blood flow, and muscle anabolic signalling at rest and after resistance exercise when co-ingested with whey protein at a dose previously shown to maximally stimulate MPS. Nine men (23.0 ± 1.9 y, 24.2 ± 2.1 kg∙m-2) performed two trials consisting of a bout of unilateral knee extension exercise (4 sets x 8-12 RM to failure) followed by ingestion of a drink containing 25g of whey protein (PRO) or 25g of whey protein-plus-50g of maltodextrin (PRO+CARB). The trials were conducted in a double-blind, randomized, cross-over fashion. Muscle biopsies and stable isotope methodology were used to measure MPS. The areas under the glucose and insulin curves were l7-fold (P < 0.05) and 5-fold (P < 0.05) greater, respectively, for PRO+CARB than for PRO. Femoral artery blood flow was increased after exercise (P < 0.05) but was not different between PRO and PRO+CARB. Exercise increased MPS (P < 0.05), but there were no differences between PRO and PRO+CARB in the resting or exercised legs. Phosphorylation of protein kinase B (Akt) was greater in the PRO+CARB than the PRO trial (P < 0.05), and phosphorylation of Akt (P = 0.05) and acetyl coA carboxylase- β (ACC; P < 0.05) was greater after exercise than at rest. There was no differential phosphorylation with exercise or condition of other proteins thought to be important in translation initiation, elongation, or mitogen activated kinase signalling pathways. In conclusion, the concurrent ingestion of 50g carbohydrate with 25g of protein did not further stimulate mixed MPS than the ingestion of the protein alone, at rest or following intense resistance exercise, suggesting that the insulinemia after protein ingestion is sufficient to fully stimulate MPS.
Keywords: Kinesiology; Kinesiology